Ecotoxicological effects of lead in ducks and geese - Mahmoud, Usama T.; Seven, Ismail; Mutlu, Seda Iflazoglu; Cicek, Miray Sila; Esen, Ahsen; Seven, Pinar Tatli (Springer, 2026)
Lead (Pb) exposure remains a critical threat to waterfowl health and conservation. This review synthesizes findings from studies published between 2015 and 2025 on Pb toxicity in geese and ducks across North America, Europe, and Asia. Ingestion of spent ammunition and Pb-contaminated sediments were identified as the predominant exposure pathways. Species-specific susceptibility was evident, with diving ducks and some geese showing higher rates of Pb shot ingestion, although all waterfowl are at risk. Acute toxicity manifested as direct mortality, emaciation, neurological disorders, and organ necrosis, while sub-lethal effects included anemia, immune suppression, impaired reproduction, altered lipid metabolism, and damage to kidneys, liver, and gut microbiota. Quantitative assessments revealed elevated Pb residues in liver, kidney, bone, blood, and feathers, with some exceeding established toxicity thresholds. Despite regional bans on Pb ammunition, legacy contamination persists in wetlands. Continued surveillance, effective policy enforcement, and mitigation strategies are essential to reduce Pb burdens in waterfowl and safeguard ecological and public health.
Keywords: Lead (Pb); Geese and ducks; Toxicity; Mitigation strategies; Immune suppression; Analytical Methods